Design Considerations for Supporting Mindfulness in Virtual Reality - Kelly, Ryan M.; Seabrook, Elizabeth M.; Foley, Fiona; Thomas, Neil; Nedeljkovic, Maja; Wadley, Greg (Frontiers in Virtual Reality, 2022)
Mindfulness practice involves bringing one's attention to the present moment and noticing events as they unfold with a non-judgmental attitude of acceptance. Although mindfulness has been shown to reduce stress and improve mental health, it can be challenging to learn mindfulness techniques. Recent years have seen an interest in using virtual reality (VR) to help people learn mindfulness by immersing users in virtual settings that support an external focus of attention and reduce everyday environmental distraction. However, the literature currently lacks an understanding of how VR should be designed to support mindfulness. In this paper we describe the iterative design and evaluation of Place, a VR app that supports mindfulness practice by situating the user in a virtual forest environment. We present findings from our design process in which prospective users trialled Place and provided feedback on the design in focus groups. Our findings draw attention to factors that influenced the user experience and acceptance of VR for mindfulness, and we describe how the design was altered to address these factors. We end by discussing key design choices that designers should consider when creating VR for mindfulness. Our contributions include insight into the importance of following an iterative design process when creating a VR mindfulness app, and a framework that can be used to inform the design of future VR apps for mindfulness practice.